QUALITY AND YIELD POTENTIAL OF SUMMER SESAME (SESAMUM INDICUM L.) AS INFLUENCED BY SOWING TIME AND NUTRIENT MANAGEMENT IN MIDDLE GUJARAT - HANSA LAKHRAN; A. C. SADHU; SANJU KUMAWAT (The Bioscan, 2015)
A Field experiment was conducted to evaluate the effect of sowing time and nutrient management on quality and yield potential of sesame during summer season of 2014. The experiment was laid out in a split plot design with four replications consisting of 15 treatments, namely, main plots: 3 sowing time (10th February, 20th February and 01st March) and sub plots: five nutrient management levels (50 % RDF + 5 t FYM ha-1, 50 % RDF + 5 t FYM ha- 1 + Bio-fertilizer, 75 % RDF + 5 t FYM ha-1, 75 % RDF + 5 t FYM ha-1 + Bio-fertilizer and 100 % RDF). The research results indicated that sowing at 20th February recorded higher yield attributes, seed and stalk yields, harvest index and quality parameters over the sowing at 10th February and 01st March. However, yield attributes except test weight, seed and stalk yields recorded at sowing 01st March was at par with sowing at 20th February whereas, sowing time had no significant effect on harvest index and oil content. Among nutrient management levels application of 75% RDF + 5 t FYM ha-1 + Bio-fertilizer (Azospyrillium + PSB) proved superior in all these parameters over remaining nutrient management levels.